MULTIVARIATE ANALYSIS OF THE MORPHOLOGICAL TRAITS OF FEMALE DUCK, MUSCOVY-DUCK AND MULE-DUCK - Johari, S.; Kusumadani, N.D.; Kurnianto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The objective of this study was to evaluate the characteristics of morphometrical measurements inthe female waterfowls. The animals used in this research were 90 ducks , 90 muscovy-ducks and 90mule-ducks in Bulukumba district of Brebes regency, Central Java, Indonesia. Parameters measuredwere maxilla length, neck length, body length, chest circumstance, wing length, chest length, femurlength and tibia length. The data were analyzed using the Statistical Analysis System ver. 9.1. Muscovyduckgenerally had the largest of size, followed by mule-duck and then duck. The most discriminantvariables were showed by chest length and chest circumstance. Muscovy-duck and mule-duck hadclosest genetic distance (3.974870) than both of the distance between duck and mule duck (14.10), andmuscovy-duck and duck (24.73). The smallest errorness level in grouping was showed in duck 1%followed by 2% in mule-duck and 3% in muscovy-duck.